2019
DOI: 10.1002/ente.201900990
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrofuran as an Oxygen Donor Additive to Enhance Stability and Reproducibility of Perovskite Solar Cells Fabricated in High Relative Humidity (50%) Atmosphere

Abstract: In sequential deposition method of lead‐halide perovskite material, the PbI2 layer morphology and remnant PbI2 play an important role in enhancing the power conversion efficiency (PCE) of the perovskite solar cell. However, humidity levels affect the PbI2 and perovskite film morphology, resulting in defect sites and recombination centers on the surface and within the bulk of the material, thus impeding the overall device performance and stability. To address this, incorporation of tetrahydrofuran (THF) additiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Reproduced with permission. [193] Copyright 2019, Wiley-VCH GmbH. Ko et al [198] used a substrate heating treatment to fabricate PSCs with a best PCE of 15.76% under 50% humidity.…”
Section: Substrate Preheatingmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [193] Copyright 2019, Wiley-VCH GmbH. Ko et al [198] used a substrate heating treatment to fabricate PSCs with a best PCE of 15.76% under 50% humidity.…”
Section: Substrate Preheatingmentioning
confidence: 99%
“…e) Top‐view SEM images of PbI 2: i) with THF additive and ii) without THF and the iii,iv) corresponding perovskites films, respectively. [ 193 ] f) J – V curve of THF treated PSCs and control group. Reproduced with permission.…”
Section: Approaches For Ambient Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The study demonstrated that THF and PbI 2 in DMF interact and form a complex, resulting in dense, homogenous, and pinhole-free film due to complex formation between the Pb and O donor from THF, because of the Lewis acid nature of Pb and Lewis basicity of THF. This, in turn, avoids a direct interaction of PbI 2 with water, improving T80 (T80 is the time at which PCE is degraded to 80% of initial PCE) for 20 days in the ambient environment, with 50% RH, when devices were exposed unencapsulated [113]. Similarly, the liquid additive diethyl ether was also found to influence the crystallization process, resulting in large grains, leading to improved photocurrent properties and performance [114].…”
Section: Ester-and Ether-based Additivesmentioning
confidence: 98%
“…Tetrahydrofuran (THF) is a non-halogenated, non-aromatic alternative to CB and toluene, which effectively dissolves HTMs, besides being also used as additive to form a superior absorber layer. [263][264][265] Wu et al determined that a smaller amount of spiro-OMeTAD is required when cast from THF rather than from CB. 266 The same group also synthesized new small molecules dissolved in THF with efficiencies of around 18%.…”
Section: Solvents For the Deposition Of The Hole Transport Layermentioning
confidence: 99%